Ventral tegmental area activation promotes firing precision and strength through circuit inhibition in the primary auditory cortex - Lou, Yunxiao; Luo, Wenzhi; Zhang, Guangwei; Tao, Can; Chen, Penghui; Zhou, Yi; Xiong, Ying (Frontiers in Neural Circuits, 2014)
The activation of the ventral tegmental area (VTA) can rebuild the tonotopic representation in the primary auditory cortex (A1), but the cellular mechanisms remain largely unknown. Here, we investigated the firing patterns and membrane potential dynamics of neurons in A1 under the influence of VTA activation using in-vivo intracellular recording. We found that VTA activation can significantly reduce the variability of sound evoked responses and promote the firing precision and strength of A1 neurons. Furthermore, the compressed response window was caused by an early hyperpolarization as a result of enhanced circuit inhibition. Our study suggested a possible mechanism of how the reward system affects information processing in sensory cortex: VTA activation strengthens cortical inhibition, which shortens the response window of post-synaptic cortical neurons and further promotes the precision and strength of neuronal activity.